Analysis of Factors of Delay in Salvage Activities in Pollution Prevention Efforts in the Waters of Nias, North Sumatra - Ramadhani, Intan Navira; Nofandi, Farisa; Sari, Eka Nurmala; Rahayu, Trisnowati (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2025)
This research discusses the delays in the salvage process of a ship with Gabon-flagged vessel that ran aground in February 2023. The ship was carrying approximately 3,600 metric tons of liquid asphalt, which posed a significant threat of marine pollution and caused damage to the marine ecosystem, including coral reefs and mangrove forests. The delay in salvage operations negatively impacted the social and economic livelihoods of coastal communities. This study employs a qualitative method with data collected through interviews and documentation. The delay factors were classified into internal factors such as limited equipment and a lack of skilled personnel at the site. External factors included weather conditions, sea waves, difficult access to the location, and the involvement of multiple institutions, which prolonged the handling time. Therefore, the study highlights the need for an integrated standard operating procedure (SOP), improved inter-agency coordination, and regulatory updates to accelerate maritime incident response and prevent further environmental degradation.